Model Komunikasi Guru dan Tenaga Kependidikan Terhadap Siswa Tunarungu di SLBN Konda - Dwi Rahayu; Nurdin Nurdin; Sitti Fauziah; Mansur Mansur (Institut Agama Islam Negeri Kendari, 2023)
ABSTRACTThis study aims to describe the communication process that occurs at Konda State Special School (SLBN), namely between teachers and education staff towards students with disabilities who are deaf. The deaf are circumstances in which one cannot hear, so one cannot speak. The method of research used in this study is qualitative descriptive, where data is gathered through observation, interview, and document study. Then, the data is analyzed by doing data reduction, data presentation, and a deduction. Informant in this study are teachers and education staff who have had direct contact with deaf student. Studies have shown that teachers and education staff implement S-R model, circular and secondary communication models, where deaf students are active when communicating with communicators both in the learning process and outside the classroom. A student with his ignorance and confusion about something will ask him directly. Then, when a communication process is challenging, a second alternative is that of using a handphone or paper as a text. It can also be seen that teachers and education staff use both verbal (oral) and nonverbal (SIBI) forms of communication simultaneously in conveying messages. In addition, the obstacles to communicating with deaf students are due to physical disabilities so as not to speak like other humans and poor language mastery, and in the learning process the deaf students forgets easly, gets bored, gets tired quickly and has difficulty concentrating. Keywords : Communication Model, Deaf Students, Education Staff, SLB, Teacher